MENINGKATKAN HASIL BELAJAR PAK MELALUI PENGGUNAAN MEDIA INFOKUS PADA SISWA KELAS X SMKN 1 ADONARA - Susana Soi Leton; Veronika Ketane Lanang (JURNAL PENDIDIKAN DAN KEGURUAN, 2025)
This research aims to improve the learning outcomes of class X students at ATPH SMKN 1 Adonara by utilizing infocus media in learning Catholic Religious Education. This research uses the Classroom Action Research (PTK) method, which is a research approach carried out by teachers with the aim of improving the quality of learning and increasing student learning outcomes. The research was conducted at SMKN 1 Adonara, Kolilanang Village, Adonara District, East Flores Regency, NTT, in September 2024. The research subjects were 9 students of class X ATPH and a teacher as researcher. To collect data, several techniques were used, namely observation, tests and interviews. The research results showed that in Cycle I, teacher activities received an average score of 3.4 (good category), while student activities received an average score of 13.33 (fairly good category). In Cycle II, the average teacher activity score increased to 4.00 (very good category), followed by student activity with the same average score, namely 4.00 (very good category). Student learning outcomes in Cycle I reached an average score of 76.11, with 5 students completing and 4 students not completing. In Cycle II, the average student score increased to 83.88, with all students (100%) achieving completeness. Based on these results, it can be concluded that the use of infocus learning media has succeeded in improving student learning outcomes in class X ATPH at SMKN 1 Adonara.